2020
DOI: 10.3390/jcm9030744
|View full text |Cite
|
Sign up to set email alerts
|

Does Combining Biomarkers and Brain Images Provide Improved Prognostic Predictive Performance for Out-Of-Hospital Cardiac Arrest Survivors before Target Temperature Management?

Abstract: We examined whether combining biomarkers measurements and brain images early after the return of spontaneous circulation improves prognostic performance compared with the use of either biomarkers or brain images for patients with cardiac arrest following target temperature management (TTM). This retrospective observational study involved comatose out-of-hospital cardiac arrest survivors. We analyzed neuron-specific enolase levels in serum (NSE) or cerebrospinal fluid (CSF), grey-to-white matter ratio by brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…Its thresholds for 0% FPR for poor outcome were ≤ 726 × 10 −6 mm 2 /s within 48 h from ROSC and ≤ 627 × 10 −6 mm 2 /s between 48 h and 7 days from ROSC, respectively. In this and another study [115], the percentage of brain volume with a low ADC (defined as an ADC value ≤ 400 × 10 −6 mm 2 /s) was assessed at a median of 3 h from ROSC [115], or within 48 h and between 48 h and 7 days from ROSC [84]. Thresholds for 0% FPR of the percentage of low-ADC brain volume were 4.3%, 2.5%, and 1.66%, respectively.…”
Section: Brain Mri (Tables 51 52 53)mentioning
confidence: 92%
See 2 more Smart Citations
“…Its thresholds for 0% FPR for poor outcome were ≤ 726 × 10 −6 mm 2 /s within 48 h from ROSC and ≤ 627 × 10 −6 mm 2 /s between 48 h and 7 days from ROSC, respectively. In this and another study [115], the percentage of brain volume with a low ADC (defined as an ADC value ≤ 400 × 10 −6 mm 2 /s) was assessed at a median of 3 h from ROSC [115], or within 48 h and between 48 h and 7 days from ROSC [84]. Thresholds for 0% FPR of the percentage of low-ADC brain volume were 4.3%, 2.5%, and 1.66%, respectively.…”
Section: Brain Mri (Tables 51 52 53)mentioning
confidence: 92%
“…However, there is no universal consensus on the best technique to assess reduced ADC within the brain after HIBI. In the four studies assessing ADC included in our review [79,84,97,115], three methods for ADC measurement were described: the mean global or regional ADC value of the brain [79,84], the proportion of voxels with low ADC [84,97,115], and the maximum size of the MRI clusters with minimum ADC [79]. In all these studies, ADC thresholds for 0% FPR were identified, often with sensitivities above 50%.…”
Section: Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Son et al’s recent study showing poor neurological outcome using DWI-MRI conducted before TTM after ROSC reported a high signal intensity in 22 of 33 (66.7%) patients [ 8 ]. One previous study reported that, while DWI is not noticeable in most patients with transient ischemic attack, BBB interruptions may exist.…”
Section: Discussionmentioning
confidence: 99%
“…Current prognostication guidelines suggest performing brain magnetic resonance imaging (MRI) 2–5 days after ROSC [ 5 ]. However, recent evidence has shown that MRI is better than brain CT at predicting neurological outcome within 3 h after ROSC [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%